The reluctant profession : homoeopathy and the search for legitimacy - Cant, Sarah [Verfasser]; Sharma, Ursula [Verfasser] (My University, 1995)
"This paper examines a group of lay homoeopaths, represented by the Society of Homoeopathy, and traces the changes that have been made to their organisation, training and knowledge as they attempt to enhance their legitimacy in the eyes of the public, government and orthodox medical profession. The group has acquired a number of 'professional' properties, but in so doing have reduced levels of freedom, marginalised factions within the group and failed to gain greater authority in the healthcare market. The homoeopaths themselves thus recognise that there are costs as well as benefits associated with their professional project and sot they have undertaken many of the changes reluctantly." (author's abstract, IAB-Doku) Der Beitrag befasst sich mit der Professionalisierung der Homöopathen in Grossbritannien. Diese waren ursprünglich als berufliche Laien angetreten. Unter dem Druck von Öffentlichkeit, Regierung und orthodoxen Medizinern haben sie sich jedoch berufsförmig organisiert und die homöopathische Ausbildung geregelt. (IAB)
Keywords: S 6.4.5.2 Übrige Gesundheitsberufe (außer Ärzte und Apotheker); G 2.3 Wandel von Arbeit & Wirtschaft; G 1.2.4 Wirtschaftszweige; S 3.5.4 Sozialpartner; G 2.5.4 Qualifizierungs- & Ausbildungskonzepte; I 2.2.1 Westeuropa; Heilpraktiker; Professionalisierung; Ausgrenzung; Berufsverband; Qualifizierung; Gesundheitsberuf; Berufsproblem; Großbritannien